The level of social support provided to orphan students in relation to their psychological tolerance in Al-Jizah district - Zaal Alzaben, Anas (Journal of Educational and Psychological Sciences, 2021)
The present study aimed at identifying the level of social support provided to orphan students in relation to their Psychological tolerance in Al-Jizah district. To achieve the goals of the study, a random sample of orphan students was selected from Al-Jizah district in the Hashemite Kingdom of Jordan, reaching 112 orphan students. Social and Psychological tolerance scale and check their psychometric properties. The results of the study found that there was a high level of social support and Psychological tolerance among orphaned students, and that there was a positive relationship between social support and Psychological tolerance , and that the students did not differ in Psychological tolerance by sex variable, but social support in males was higher than females students, and based on the results of the study Some recommendations were made, including working on the forms of social support and Psychological tolerance among orphan students and their development through extension programs.
Keywords: social support; Psychological tolerance; orphan students